Dinamika Pemikiran Hukum Islam Kontemporer dalam Perspektif Modernitas - Muh Fadhil Amir; Syekh Alfath; Mahaputra Dwi S; Kurniati Kurniati (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Modernity brought about a fundamental change in the way of looking at laws, authorities, and state systems, which also influenced the existence of Islamic law. Islamic law as a normative system that comes from revelation is faced with epistemological challenges due to the dominance of modern rationality and positive state laws. This article aims to analyze the dynamics of contemporary Islamic legal thought in response to modernity, focusing on changes in legal epistemology, transformation of ijtihad methodology, and the relationship between Islamic law and the modern legal state. This research uses normative legal research methods with conceptual and historical approaches. The results of the study show that contemporary Islamic legal thought is not static, but rather undergoes renewal through a contextual approach and the use of maqāṣid al-syarī'ah as the main methodological framework. Moreover, Islamic law in the context of the modern legal state is more geared towards the internalization of substantive values into the national legal system than symbolic formalization. Thus, the dynamics of contemporary Islamic legal thought are an effort to maintain the relevance of Islamic law so that it remains in line with the principles of justice, benefit, and constitutionalism in the modern era.